The Effectiveness of Teaching Materials Based on Local Culture on 7th Grade Students in Junior High School Sipirok - Muhammad Riswan Nasution; Wisman Hadi; Syahnan Daulay (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The study deals with the effectiveness of teaching materials based on local culture on 7th grade students in junior high school Sipirok. The study was conducted at one of Junior High Schools 1 in Sipirok located in South Tapanuli Regency. Student learning outcomes are obtained by providing a trial test using instructional materials that have been developed which aims to see the extent to which increased student understanding of the Sipirok local culture-based text description learning material by using teaching materials developed in this study. Student learning outcomes based on pretest and posttest show the difference in the difference from pretest to posttest the score obtained 10.42 with an average pretest 75.65 on the criteria of "good" and an average posttest of 90.8 on the criteria of "very good". It can be concluded that learning using on Sipirok local culture-based text descriptions can improve student learning outcomes in Indonesian language subjects especially description text material.